Criminal Liability for Human Trafficking Offenders Through the Non-Procedural Placement of Indonesian Migrant Workers - Alya Silva Baskara; Hartiwiningsih; Rehnalemken Ginting (CV Edujavare Publishing, 2026)
The non-procedural placement of Indonesian Migrant Workers (PMI) remains a serious issue because it has the potential to result in exploitation, violence, and the crime of trafficking in persons. Such practices are generally carried out through illegal recruitment, the use of forged documents, and the deployment of migrant workers without complying with applicable legal procedures. This study aims to analyze the regulation of Indonesian positive law concerning the criminal offense of non-procedural placement of PMI and to examine the construction of criminal liability of its perpetrators from the perspectives of criminal law and trafficking in persons. This research employs a normative legal research method using statutory, conceptual, and case approaches. The findings indicate that the regulation of non-procedural placement of PMI is governed by Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers and is closely related to Law Number 21 of 2007 concerning the Eradication of the Crime of Trafficking in Persons. Criminal liability may be imposed where the elements of criminal responsibility, fault, and the absence of grounds for the exclusion of criminal liability are fulfilled. Furthermore, where elements of exploitation, fraud, or abuse of the victim’s vulnerable position are present, perpetrators may also be prosecuted under the Anti-Trafficking Law. Therefore, the complementary application of both laws is necessary to ensure optimal legal protection for Indonesian Migrant Workers.